Simvastatin treatment reduces the cholesterol content of membrane/lipid rafts, implicating the N -methyl-D-aspartate receptor in anxiety: a literature review - Júlia Niehues da Cruz; Débora Delwing Dal Magro; Daniela Delwing de Lima; José Geraldo Pereira da Cruz (Universidade de São Paulo, 2017)
ABSTRACT Membrane/lipid rafts (MLRs) are plasmalemmal microdomains that are essential for neuronal signaling and synaptic development/stabilization. Inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme-A reductase (statins) can disable the N-methyl-D-aspartate (NMDA) receptor through disruption of MLRs and, in turn, decrease NMDA-mediated anxiety. This hypothesis will contribute to understanding the critical roles of simvastatin in treating anxiety via the NMDA receptor.